FPGA/Embedded system training kit targeted to graduate students towards industry level short training - Islam S.Z.; Jidin R.B.; Islam S.Z.; Hamid F.A.B. (2023)
The wide application of embedded systems become a trend in the post-PC era. In the College of Engineering, Universiti Tenaga Nasional (UNITEN), embedded system education is one of the characteristic subjects, so "practical training" is the brand new characters as the most important process in the embedded system education towards industrygeared training. The training is an on-campus process toward gaining the practical experiences which are suitable for the real engineering design or IT related companies, especially so for the students without past work experiences. Practical training using single industrial grade kits on embedded system has expanded to most Electrical and Electronic Engineering for both undergraduate and graduate students. The course has been updated towards industry employees training especially to meet their design aspects. Embedded systems course have been deployed in numerous fields which have different requirements of embedded systems architecture. In this paper, a project-based learning strategy using single training kit is proposed as a pedagogical tool for embedded system education. The proposed project-based learning can motivate students to integrate and formulate the multi-disciplinary knowledge previous learned into a real-world embedded system project development. The course development focused on lecture-lab integration and laboratory learning. Course and lab activities were designed using a learning model that captures lower-order and higher-order cognition levels of Bloom's taxonomy. 2010 IEEE.